Randomized controlled trial comparing efficacy between a vaginal misoprostol loading and non-loading dose regimen for second-trimester pregnancy termination - Saipin Pongsatha (2018)
Aim: The aim of this study was to compare the efficacy of vaginal misoprostol loading dose regimen with non-loading dose regimen for termination of second-trimester pregnancy with live fetuses. Material and Methods: A randomized controlled trial was conducted on pregnant women with a live fetus at 14-28 weeks. The patients were randomly allocated to receive either the vaginal misoprostol loading dose regimen (600 mcg, then 400 mcg every 6 h) or the non-loading dose regimen (400 mcg every 6 h). Failure to abort within 48 h was considered to be a failure. Results: Of 157 recruited women, 77 were assigned to be in group 1 (loading group) and 80 were in group 2 (non-loading group). The median abortion time was not statistically different between the groups (14.08; 95% confidence interval: 12.45-17.77 h and 14.58; 95% confidence interval: 12.8-17.27 h, P > 0.05). The rates of abortion within 24 h and 48 h were also comparable between the groups. Fever and chills were more common in the loading group. No other serious complications, such as postpartum hemorrhage and uterine rupture, were found. Conclusion: Vaginal misoprostol in the loading dose regimen had a similar efficacy to the non-loading dose regimen but was associated with more adverse maternal effects. © 2013 Japan Society of Obstetrics and Gynecology.